"Diseño de un sistema de riego automático para un vivero de plantas de tabaco, con estructura soportante móvil" - Valarezo Anchundia, Anyhony Alberto (2019)
Automated irrigation within a nursery represents many improvements compared to conventional irrigation, which is why the present study aimed to design a mobile irrigation system for a tobacco plant nursery, with a mobile supporting structure. The preparation of this work arises from the problem located in the company Ecuacapa SA, between the Cristal and San Luis enclosures of the Zapotal canton, located in the province of Los Ríos, between the coordinates 1 ° 21'20.4 "South latitude and 79 ° 22 ' 56.7 "West length. The design of the automated irrigation system in the tobacco nursery was carried out in SOLIDWORKS 2017, while the simulation of the engine operation at the time of making the turn or direction change was carried out in CADE_SIMU V3.0. SAP2000 was used for the structural analysis. The amount of water that will be used in the irrigation system will be 1126.4 l / day, for 60 days, supplying the water driven by a 0.75 HP hydraulic pump to irrigate with 8 nebulizers to 992 trays of 128 cells. The irrigation system will consist of a fixed structure 56 m long, 8.75 m wide and 2.70 m high, while the irrigation wing will be constructed of 50x25x2 and 50x25x3 C profiles, on which the conductive network of PVC, the same that due to the characteristics and dimensions of the selected materials will withstand the pressure and efforts of work. The cost benefit analysis showed that when conventional irrigation is used, a profit of $ 0.84 is obtained for each dollar invested (cost benefit ratio of 1.84), while with automated irrigation this gain is increased by $ 0.11 for each dollar invested (benefit ratio cost of 1.95) with respect to conventional irrigation, having a useful life of 15 years. 7 planes were made, 1 general plane in which the irrigation system is recorded, 4 assembly planes, 100-1 plane in which the structure of the engine consists, 100-2 where the structure of the irrigation wing is detailed, 100- 3 where the irrigation wing pipe is shown, 101-4 in which the structure of the irrigation system is located and 2 subset planes of the 100-1 plane, in the 100-1.1 plane the base of the structure of the structure is detailed engine and in the plane 100-1.2 you will find the details of the motor base support. Key words: tobacco growing, greenhouse, automated irrigation